The dialectic of the relationship between good governance and achieving sustainable development (Case study of Afghanistan( (قضايا سياسية, 2024)
Good governance plays an important role in building a person and a state. Political systems that are capable of preserving the basic values of individuals, such as justice, freedom, and equality, ensure the building of a strong state in all economic, social, political, administrative, and legal aspects, as building strong legal institutions helps to establish a pattern of governance characterized by legitimacy. By the people and can achieve sustainable development, there is a direct relationship between them, and sustainable development cannot be separated from good governance, as it is not possible to reach high levels of sustainable development without a high and sublime level of good governance.The success or failure of any country's efforts to enhance the level of sustainable development is closely linked to the nature and level of good governance, and the latter constitutes the establishment of a sound environment for economic, social and human development.Implementing good governance is no longer a voluntary issue, but rather a necessity to meet the requirements and interests of all relevant parties. It enhances the process of social harmony and justice, provides room for creativity and excellence, provides a level of legitimacy in the local community, and achieves a level of efficiency and cooperation among individuals and municipalities to create a supportive social environment.